Pengembangan Media Pembelajaran Sistem Saraf Dengan Menggunakan Adobe Flash CS3 pada Siswa Kelas XI Sekolah Menengah Atas - Arisetya, Dian; Djulia, Ely; Hasruddin, Hasruddin (Magister Pendidikan Biologi, Universitas Negeri Medan, 2016)
This study was intended to: (1) identify the development of learning media procedure nervous system with Adobe Flash CS3 for XI grade high school student; (2) figure up the studentâs responds to learning media development of nervous system with Adobe Flash CS3 for XI grade high school student. This study was classified as Borg & Gall model development that included to 6 steps (1) Information collection; (2) Designing; (3) pre-product development; (4) expert validation; (5) revision; (6) post product testing. The subject of this research was XI grade high school student of SMA N 1 Rantau Selatan LabuhanBatu at 2012/2013 academic year. This study was designed by questionnaire method (Linkert scale) that administered for testing to two media experts, two matter experts, three personals, 9 small groups, and 30 bounded field. The collected data was analyzed by applying descriptive analysis, qualitative analysis andÂ Â inferential analysis by employing SPSS version software 19.0 for Windows. The analysis revealed the test by (1) learning media experts (89%); (2) learning biology matter expert (83%); (3) personal (83%); (4) small groups (91%); (5) bounded field (94%). The scores indicate that responses from media experts, matter experts and student to biology learning media development with Adobe Flash CS 3 for nervous system for high school student is very good categorized.